Betibeglogene autotemcel gene therapy in patients with transfusion-dependent, severe genotype β-thalassaemia (HGB-212): a non-randomised, multicentre, single-arm, open-label, single-dose, phase 3 trial - Kwiatkowski, Janet; Walters, Mark C; Hongeng, Suradej; Yannaki, Evangelia; Kulozik, Andreas; Kunz, Joachim; Sauer, Martin G; Thrasher, Adrian J; Thuret, Isabelle; Lal, Ashutosh; Tao, Ge; Ali, Shamshad; et al. (The lancet, 2024)
Background - Transfusion-dependent β-thalassaemia (TDT) is a severe disease, resulting in lifelong blood transfusions, iron overload, and associated complications. Betibeglogene autotemcel (beti-cel) gene therapy uses autologous haematopoietic stem and progenitor cells (HSPCs) transduced with BB305 lentiviral vector to enable transfusion independence. - Methods - HGB-212 was a non-randomised, multicentre, single-arm, open-label, phase 3 study of beti-cel in patients with TDT conducted at eight centres in France, Germany, Greece, Italy, the UK, and the USA. Patients with β0/β0, β0/β+IVS-I-110, or β+IVS-I-110/β+IVS-I-110 genotypes, clinically stable TDT, and a transfusion history of at least 100 mL/kg per year of packed red blood cells (pRBCs) or at least eight transfusions of pRBCs per year in the 2 years before enrolment were eligible for participation. After undergoing HSPC mobilisation and busulfan-based, pharmacokinetic-adjusted myeloablative conditioning, patients were infused with beti-cel and followed up for 24 months. The primary efficacy outcome was transfusion independence, defined as weighted average haemoglobin level of 9 g/dL or above without pRBC transfusions for 12 or more months. The primary outcome was measured in all patients who received an infusion of beti-cel (transplant population); safety was evaluated in all patients who initiated study treatment (intention-to-treat population). Patients were eligible to enrol in the ongoing 13-year long-term follow-up study (for a total of 15 years), LTF-303 (registered at ClinicalTrials.gov, NCT02633943). This trial, HGB-212, was registered at ClinicalTrials.gov (NCT03207009), and is complete. - Findings - From June 8, 2017, to March 12, 2020, 20 patients were screened for eligibility. One patient was ineligible and one withdrew consent before HSPC mobilisation and myeloablative conditioning. Of the 18 patients who received beti-cel, ten (56%) were male and eight (44%) were female; 13 (72%) were younger than 18 years at the time of informed consent, and five (28%) were older than 18 years. 12 (67%) patients had β0/β0 genotypes, three (17%) had β0/ β+IVS-I-110, and three (17%) had β+IVS-I-110/β+IVS-I-110. As of Jan 30, 2023, all patients enrolled in the long-term follow-up study and the median follow-up was 47·9 months (range 23·8-59·0). All 18 patients were evaluable for transfusion independence, with 16 (89%) of 18 reaching and maintaining transfusion independence to last follow=up (estimated effect size 89·9% [95% CI 65·3-98·6]). All patients had at least one adverse event after beti-cel infusion. There were no serious adverse events considered to be related to beti-cel, and no deaths. - Interpretation - These data demonstrate that beti-cel can allow patients with genotypes that cause severe β-thalassaemia (β0/β0, β0/β+IVS-I-110, or β+IVS-I-110/β+IVS-I-110) to reach transfusion independence. Beti-cel offers the potential to attain near-normal haemoglobin levels for those with severe forms of TDT, and a potentially curative option without the risks and limitations of allogeneic HSPC transplantation. Patients are being followed up for a total of 15 years to assess the durability of transfusion independence and long-term safety profile of beti-cel. - Funding - Bluebird Bio, Somerville, MA, USA.
Online verfügbar: 8. November 2024, Artikelversion: 29. November 2024
Gesehen am 10.06.2025